The Composition “Upon the Right Hand Did Stand the Queen” and the Hypothesis of the Novgorodian and Balkan Relations in the Mural Painting of the 14th Century - Nemykina, Elena A. (Actual Problems of Theory and History of Art, 2013)
Analysis of the iconographic features of the fresco composition “Upon the right hand did stand the Queen” from the church of Transfiguration in Kovalevo near Novgorod (1380) and investigation of its origins gives us the opportunity to look at the entrenched hypothesis of the Novgorodian and Balkan relations in the mural painting of the 14th c. from a new perspective. More detailed consideration of this theme gives grounds to question some statements of this hypothesis including the appropriateness of comparing of the Novgorodian murals of the 14th c. with the Balkan ones.